Estudo de estatística no ensino médio: uma proposta de ensino através da análise de dados sociais e ambientais - Fortes, Diogo Cesar (2014)
This work presents a proposal to Statistics teaching for High School in an interdisciplinary way. Analyze data from the Municipal Human Development Index Gaucho some cities and climate in some Brazilian cities, seeking to explore the most of what's statistic in these matters. Seek to understand the basic topics of statistics provided in the curriculum, noting that the application of mathematics to diverse areas of knowledge. We will use spreadsheets as a technological tool to support teaching.